Synthesis of borate-based epoxy molding compound for radiation hardened electronics packaging - Muhammad Ridhwan Md Yusoff (2014)
Recently, considerable attention has been focused on the development of a new class of shielding material made from a mixture of epoxy resin and boron oxide (B2O3). This material exhibits better shielding performance than existing materials thus making it suitable for use in radiation machineries and space applications.